(untitled) (Proceedings of Scientific Conference on Multidisciplinary Studies, 2023)
This article explores the fundamental goals and objectives of the science of Clinical Anatomy, delving into its relevance and significance in the field of medicine. A comprehensive literature analysis, methodologies employed, results obtained, and a detailed discussion are presented to elucidate the crucial role Clinical Anatomy plays in medical education, patient care, and surgical advancements. The article concludes with insights and suggestions for further research and development in this vital discipline.